(untitled) (Philology, 2023)
The 40th commemoration of the launch of the Indian Studies Programme at Sofia University was marked with a three-day national conference featuring international participation under the title “Narrating India: Traditions, Attitudes and Directions”, which was held from October 16 to 18, 2023.